Sustainable Development Goals: Strengthening rural-urban linkages is the key for India - Fan, Shenggen; Joshi, Pramod Kumar (2017)
The world is rapidly urbanising. Currently, more than half of the world’s population lives in urban areas, and by 2050, as much as 66% is projected to be urban, with much of this rise taking place in developing countries. India is no exception: 33% of the population is urban and will rise to 50% by 2050.